Interactive Multimedia Innovation: Increasing the Interest in Learning of Children With Multiple Disabilities in Early Age - Elsiana Nurjannah, Yunita; Ervin, Ervin Nurul Affrida (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
Children who are deaf are children who experience hearing problems or obstacles which cause them to have difficulty communicating and receiving language information through hearing. Children who experience communication barriers can result in children experiencing intellectual disorders. The aim for this research to analyze problem of children's interest in learning in early childhood who experience hearing impairments (deaf and intellectually impaired) through interactive multimedia learning. The research method uses a literature study research method by reviewing various sources in the form of journals, research results and published books. The results show that interactive multimedia plays a very positive role in increasing the learning interest of children with special needs (deaf-impaired) from early age. Through of interactive learning multimedia, children become more enthusiastic and focused during the learning process so that it is believed that children will easily grasp the message from the learning delivered.